SISTEM PENUNJANG KEPUTUSAN PEMILIHAN KEPALA SEKOLAH DENGAN MENGGUNAKAN METODE SAW - Arbi Haryanto; Irfan Maulana; Muhamad Latief; Muhammad Akbar Nuansaadjie (CV. Multi Kreasi Media, 2023)
Teachers have an important role in improving the quality of students in developing student competencies. Teachers who have good competence should be promoted as school principals. Assessment of teacher work is displayed through the mastery of professional, personality and social competencies. The selection of school principals is very important because the principal is the highest leader who is very influential on the progress of the school. This study aims to provide recommendations to schools to select teachers who deserve to be promoted as school principals using the Simple Additive Weighting ( SAW ) . Based on this research, it shows that the implementation of a decision support system can help schools to select teachers who are worthy of being principals in a short time.